THE EFFECTIVENESS OF SELF-ACCUPRESURE GUIDANCE ON THE REDUCTION OF PRIMARY DYSMINOREA PAIN - Hurin'in, Nur Maziyah; Indah, Siti Nur (UNIVERSITAS AIRLANGGA, 2025)
Background: Incidence rates of Dysmenorrhea is average over 50% worldwide, with Indonesia reporting 55% and East Java specifically showing a prevalence of 71.3%. Dysmenorrhea can reduce sleep quality and have an impact on changes in a person's mood which will cause stress, depression and anxiety. The aim of this study was to determine the effect of self-accupressure guidance on reducing primary dysmenorrhoea pain in adolescent girls. Method:. This was a quasi-experimental design with a one-group pretest-posttest approach. The study population comprised all 66 female students at Manbail Futuh Vocational School. A purposive sampling technique was utilized to select participants who met specific inclusion criteria.This selection process resulted in a sample of 18 adolescent girls. Participants received standardized self-acupressure guidance. The intervention involved a structured guidance session followed by a period where participants were encouraged to practice self-acupressure daily during their menstrual cycle. Pain intensity was measured using a validated numerical rating scale (NRS) before the intervention and after the intervention, specifically during their subsequent menstrual period. The effectiveness of the self-acupressure guidance was assessed by comparing the pretest and posttest pain scores. Result: The results of the Wilcoxon test using SPSS For Windows software with a level of significance obtained p-Value 0.001 < 0.05. Based on the above, it is proven that there was an influence of self-accupressure guidance on reducing primary dysmenorrhea pain experienced by young women. Conclusion: Self-acupressure guidance was effective in reducing the intensity of dysmenorrhea in adolescent girls. This research can be used as one of the interventions in treatment other than using drugs.